Peran Serta Masyarakat dalam Pengelolaan Sampah Domestik sebagai Upaya Pencegahan Penyakit Berbasis Lingkungan - Widiyanto, Agnes Fitria; Kurniawan, Arif; Gamelia, Elviera (Universitas Ahmad Dahlan, 2018)
Background: Domestic waste remains a problem in Indonesia. The more the population who were making the volume of domestic waste increase, including in Banyumas regency. The purpose of this study is to describe the knowledge, attitude, and practice of the community in the management of domestic waste as an environmental-based disease prevention. Method: The method that was used in this research is qualitative. The research subjects were obtained by using purposive sampling technique by interviewing 7 people as the main research subject and 3 midwives, Forum Kesehatan Desa (FKD) Chairman, and Tempat Pembuangan Akhir (TPA) Manager as the supporting research subject. How to collect data with observation, in-depth interview, literature study, and documentation. This model of analysis is an interactive analysis, through the process of collected data in the form of research findings that are relevant to the writing materials, and then presented in a narrative. Results: The results showed that the community has applied the knowledge about domestic waste as an environmental-based disease prevention. Conclusion: Environmental-based disease prevention requires policies and human resources in the application.